The Effectivity Of Science Uno Card-Assisted CIRC Method To Classification And Scientific Communication Skills - Dewi, Novi Ratna; Pamelasari, Stephani Diah; Hidayati, Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This study intended to examine the effectivity of science uno card-assisted CIRC method on solar system topic to classification and scientific communication skills. This is experimental research whose sample consisted of two classes; one as an experimental group and the other as a control group. The data of students’ classification skills were gathered from posttest score on cognitive learning outcomes arranged based on four indicators. Observations were carried out in three-time learnings to obtain the data of scientific communication. The analysis of t-test of the total score of classification skills resulted in tcount=2.29 and ttable=2.00, meaning that the experimental group’s classification skills were better than the control group. A Mann Whitney differential test of the total score of scientific skills resulted in Zcount=4.83 and Ztable=1.69 meaning that there was a difference of communication skills between the two classes. Based on the research results, it could be said that science uno card-assisted CIRC method on solar system topic was effective in improving classification and scientific communication skills.